Geriatric-focused education for community health workers: a dementia training that effectively provides knowledge and skills to address dementia within the scope of practice of this public health workforce - Reinschmidt, Kerstin M.; Alhay, Zahra A.; Kleszynski, Keith L.; Jennings, Lee A. (Frontiers in Public Health, 2025)
BackgroundIn light of the public health crisis of dementia, community health workers (CHWs) have increasingly received national attention as a public health workforce that can support individuals, families, and communities in preventing, recognizing, and living with dementia. With training, CHWs have high potential for making a positive impact on healthy aging and living with dementia. Recognizing the need for a CHW-specific training, the Oklahoma Dementia Care Network (OkDCN) developed the Dementia Training for Community Health Workers. This paper examines the training program’s pedagogical framework and comprehensive evaluation processes, tools, and outcomes.MethodsThis training was developed as a train-the-trainer model combining didactic instruction with adult learning strategies. The training’s content resulted from combining knowledge about CHWs in Oklahoma, National C3 Council recommendations on the CHW scope of work, and evidence-based dementia care strategies. The evaluation design measures effectiveness focused on the first three levels of the Kirkpatrick Model, i.e., CHW training feedback, knowledge and skill acquisition, and application of the training knowledge and resources. The OkDCN collaborated with CHWs to develop and implement the training.ResultsBetween June 2020 and March 2024, we conducted 15 trainings with a total of 307 trainees. Data collected on pre/post knowledge, self-efficacy, and post-training feedback were analyzed as a subsample of the total number of trainees. Among this subsample (50%; n = 154) both knowledge and some of the self-efficacy items showed statistically significant improvements. Overall, trainees were satisfied with the training in terms of content, format, and delivery. A follow-up survey showed that trainees appreciated the practical value of the training for their jobs and used the information in their day-to-day work, but did not yet conduct dementia trainings in their communities.ConclusionAs CHWs are tasked with alleviating the public health crisis of dementia, they necessitate geriatric-focused education that is evidence based, workforce-appropriate, and adaptable to diverse communities. Designed specifically for CHWs as a peer-implemented train-the-trainer model, this innovative training contributes to both workforce development and health equity. CHWs who apply or pass on their knowledge can make positive impacts on their communities’ healthy aging.